2021
DOI: 10.3389/fimmu.2021.704427
|View full text |Cite
|
Sign up to set email alerts
|

Protectins PCTR1 and PD1 Reduce Viral Load and Lung Inflammation During Respiratory Syncytial Virus Infection in Mice

Abstract: Viral pneumonias are a major cause of morbidity and mortality, owing in part to dysregulated excessive lung inflammation, and therapies to modulate host responses to viral lung injury are urgently needed. Protectin conjugates in tissue regeneration 1 (PCTR1) and protectin D1 (PD1) are specialized pro-resolving mediators (SPMs) whose roles in viral pneumonia are of interest. In a mouse model of Respiratory Syncytial Virus (RSV) pneumonia, intranasal PCTR1 and PD1 each decreased RSV genomic viral load in lung ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 44 publications
(116 reference statements)
1
29
0
Order By: Relevance
“…Here, the discordant kinetics for viral clearance and pathogen-initiated inflammatory responses are indicative of an excessive and prolonged induction of genes for viral host defense that persisted long after their essential roles in viral clearance and suggest a risk window of adaptive homeostasis, where intervention with proresolving mediators that dampen IFN signaling could mitigate post-IAV risk for secondary bacterial infection. Along these lines, DHA-derived protectins, a related family of SPMs, can decrease IFN expression after mouse respiratory syncytial virus infection ( 43 ). Additionally, harnessing proresolving pathways with SPMs, including MCTR3, was recently shown to reverse leukocyte defects in patients with severe COVID-19 ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, the discordant kinetics for viral clearance and pathogen-initiated inflammatory responses are indicative of an excessive and prolonged induction of genes for viral host defense that persisted long after their essential roles in viral clearance and suggest a risk window of adaptive homeostasis, where intervention with proresolving mediators that dampen IFN signaling could mitigate post-IAV risk for secondary bacterial infection. Along these lines, DHA-derived protectins, a related family of SPMs, can decrease IFN expression after mouse respiratory syncytial virus infection ( 43 ). Additionally, harnessing proresolving pathways with SPMs, including MCTR3, was recently shown to reverse leukocyte defects in patients with severe COVID-19 ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…RSV infection increase the levels of leukotrienes, 5-LO (Behera et al, 1998), COX-2, and PGE2 (Walker et al, 2021), and treatment with COX-2 inhibitors decreases lung pathology associated with RSV infection (Richardson et al, 2005). Intranasal administration of the SPM, protectin D1 (PD1) and protectin conjugates in tissue regeneration 1 (PCTR1), reduce viral load during RSV infection (Walker et al, 2021). Also, consumption ômega-3 during pregnancy, the precursor for RvDs production, can protect the offspring children under the age of two from asthmatic symptoms and respiratory infections (Bisgaard et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, topical application of PCTR1 (100 ng/day) to mice with full-thickness dorsal skin wounds, showed enhanced wound closure in the early stages of wounding, in accordance with accelerated keratinocyte migration [32]. Recently Levy and co-workers, using a mice model of respiratory syncytial virus (RSV) pneumonia, reported that PCTR1 and PD1 each reduced the viral load in mice, dampening lung inflammation significantly [33]. Moreover, when PCTR1 was administrated post-infection, the levels of eosinophils, neutrophils and NK cells were all reduced; the same was observed for the interferon-gamma production by lung CD4 + T cells [33].…”
Section: Structure-functions Of the Protectinsmentioning
confidence: 98%
“…Recently Levy and co-workers, using a mice model of respiratory syncytial virus (RSV) pneumonia, reported that PCTR1 and PD1 each reduced the viral load in mice, dampening lung inflammation significantly [33]. Moreover, when PCTR1 was administrated post-infection, the levels of eosinophils, neutrophils and NK cells were all reduced; the same was observed for the interferon-gamma production by lung CD4 + T cells [33]. Of interest, PCTR1 and PD1 each enhanced interferon-lambda expression in human bronchial epithelial cells.…”
Section: Structure-functions Of the Protectinsmentioning
confidence: 99%
See 1 more Smart Citation